Relações entre os estilos parentais e juízo moral de adolescentes - Kadooka, Aline [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Studies on how parents are educating their children have been conducted in the parenting styles approach. Parents are responsible for providing the first information to the children, because in the preschool period are primarily responsible for the provision of material and emotional resources. In educational practice, the parents when interact with their children or through their own behavior, transmit norms and values to children and adolescents and therefore contribute to the moral development of the same. In educational practice, the parents when interact with their children or through their own behavior, transmit norms and values to children and adolescents and therefore contribute to the moral development of the same.This interaction influences in the repertoire of tools that will be used to cope with the different situations in life. The rules, actions, judgments and values that parents express contribute to the mode of being of the child. From the point of view of moral psychology,, parents can be good or bad models, since they are inevitably their examples. When teens practice and experience the rules in accordance with the cooperation and not by external pressures or obedience, they are able to elaborate them differently. Hence the importance of mutual respect and dialogue for the way to the moral autonomy. This study aimed to analyze the relationship between moral reasoning teens and parenting styles. Participated in this study 55 adolescents between 11 and 17 years enrolled in a Social Program Assis-SP. To achieve the proposed objectives, we use as instruments the Respondingness and Demandingness Scale and the Defining Issues Test (DIT-2). It is worth mentioning that the Scheme of Interest Staff comprises the lower levels of moral development, ie the pre-conventional level. The results obtained in this study indicate that the participants mainly showed a level of pre-conventional and conventional moral reasoning. In relation to...

Estudos sobre como os pais estão educando os seus filhos têm sido realizados na abordagem de estilos parentais. As primeiras informações que as crianças recebem, normalmente são advindas deles, pois na fase pré-escolar são os principais responsáveis pelo provimento de recursos materiais e afetivos. Na prática educativa os pais ao interagirem com seus filhos ou por meio de seus próprios comportamentos, transmitem normas e valores às crianças e aos adolescentes e, portanto, influenciam o desenvolvimento moral dos mesmos. Essa interação influencia no repertório de ferramentas que serão utilizadas para o enfrentamento das diferentes situações da vida. As regras, as ações, os julgamentos e os valores que os pais expressam contribuirão para o modo de ser da criança. Do ponto de vista da psicologia da moral, os pais podem ser bons ou maus modelos, já que são inevitavelmente seus exemplos. Quando os adolescentes praticam e vivenciam as regras de acordo com a cooperação e não por pressões de forças externas ou obediência, são capazes de elaborá-las de maneira mais consciente. Daí a importância do respeito mútuo e o diálogo para o percurso até a autonomia moral. O presente estudo teve como objetivo analisar as relações entre o raciocínio moral de adolescentes e os estilos parentais. Participaram dessa pesquisa 55 adolescentes entre 11 e 17 anos matriculados em um Programa Social do município de Assis-SP. Para atingir os objetivos propostos utilizamos como instrumentos a Escala de Exigência e Responsividade e o Defining Issues Test (DIT-2). Convém ressaltar que o Esquema de Interesse Pessoal, compreende os níveis mais baixos de desenvolvimento moral, ou seja, o nível pré-convencional. Os resultados obtidos nessa pesquisa apontam que os participantes apresentaram principalmente um nível de raciocínio moral pré-convencional e convencional. Já em relação aos estilos...
Keywords: Educação - Participação dos pais; Pais e filhos; Adolescentes; Desenvolvimento moral; Adolescentes - Relações com a familia; Crianças - Relações com a familia; Education